Answer:
x = 0,
y = -3
Explanation:
Let us solve through elimination ~
1. Multiply top equation -5x + y = -3 by 8, adding that product to the bottom equation 3x - 8y = 24:
8 ( -5x + y = -3) ⇒ - 40x + 8y = -24
+ 3x - 8y = 24 + 3x - 8y = 24
2. To further express this algebraic process of adding to find x in this case:
- 40x + 8y = -24 ⇒ - 37x = 0 ⇒ x = 0
+ 3x - 8y = 24
3. Now let us substitute this value of x into the top equation -5x + y = -3:
- 5 ( 0 ) + y = - 3
4. ...And solve for y:
- 5 ( 0 ) + y = - 3 ⇒ 0 + y = -3 ⇒ y = -3